Test IMPLEMENTASI TEKNOLOGI DIGITAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM : Penerapan Internet of Things dalam Pendidikan Agama Islam - Hamzah Irfanda Irfanda; Heru Triasnawa; Muhammad Rafi Ahadi (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
The Implemtasion of digital technology in Islamic Religious Education (PAI) contributes positively to improving the quality of the teaching and learning process in terms of student interest, flexibility, collaboration, and evaluation effectiveness. Through interactive media, online learning platforms, and Islamic educational applications, Islamic Religious Education material can be delivered in a more engaging and contextual manner that aligns with the characteristics of the digital generationThis study aims to describe the implementation of digital technology in Islamic Religious Education (PAI) learning. The study employs a qualitative approach using a literature review method. The findings reveal the concept of digital technology in education, forms of its implementation in Islamic Religious Education learning, the advantages gained, challenges faced, and strategies to strengthen the implementation of digital technology in Islamic Religious Education instruction